2005
DOI: 10.1007/s00540-005-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olprinone on hepatosplanchnic circulation and mitochondrial oxidation in a porcine model of endotoxemia

Abstract: Our data for this porcine endotoxemia model suggest that olprinone may have beneficial therapeutic effects in restoring not only systemic and hepatic circulation but also mitochondrial oxidation in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…29 It has been reported that olprinone showed antiinfl ammatory eff ects in experimental models of myocardial ischemia-reperfusion injury, 30 lipopolysaccharide-induced lung injury, 31 ischemiareperfusion-induced acute renal injury, 16 and endotoxic shock. 32 In the present study, patients in the olprinone group showed signifi cantly lower WBC counts and CRP levels aft er surgery compared with the placebo group.…”
Section: Discussionmentioning
confidence: 91%
“…29 It has been reported that olprinone showed antiinfl ammatory eff ects in experimental models of myocardial ischemia-reperfusion injury, 30 lipopolysaccharide-induced lung injury, 31 ischemiareperfusion-induced acute renal injury, 16 and endotoxic shock. 32 In the present study, patients in the olprinone group showed signifi cantly lower WBC counts and CRP levels aft er surgery compared with the placebo group.…”
Section: Discussionmentioning
confidence: 91%
“…Olprinone induces relaxation of RGEA and internal thoracic artery [8] and decreases the rhythmical contraction of the RGEA as effectively as diltiazem [9]. Olprinone also enhances hepatosplanchnic blood flow and increases hepatic oxygen delivery [10,11], which might be advantageous during liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In a porcine model of endotoxemia, endotoxin decreased the cardiac index and hepatic oxygen delivery (DO2H), while oxygen consumption (VO2H) was unchanged. Treatment with PDE3 inhibitor olprinone unchanged cardiac index, but elevated DO2H and VO2H indicating a restoration of hepatic circulation, and prevented LPS-induced reduction of cytochrome aa3 and increase in arterial lactate values [135] (Table 4). Vasodilating effects of olprinone on peripheral and pulmonary vessels in hypoxic conditions were shown in a canine model of hypoxic pulmonary hypertension where intravenous olprinone increased heart rate and decreased mean aortic pressure, mean pulmonary arterial pressure, pulmonary vascular resistance, systemic vascular resistance, and right ventricular stroke work index, without the change in cardiac index [136].…”
Section: Pde3 Inhibitorsmentioning
confidence: 96%